IoT-based for Monitoring and Control System of Composter to Accelerate Production Time of Liquid Organic Fertilizer - Safira Firdaus Mujiyanti; Putri Yeni Aisyah; Adelia Firsty Salsabilla; Tiffany Rachmania Darmawan; Abdul Rohid (IPTEK The Journal of Engineering, 2022)
The composter is a method to produce the liquid organic fertilizer. The manual process certainly takes a long time. Thus, the automatic composter proposed in this research is equipped with a monitoring and control system. In producing liquid organic fertilizer using a composter, there are several things that can affect the maturity of the fertilizer, including pH and temperature factors. The reference temperature for produce liquid organic fertilizer in the composting process ranges from 30-40 oC, while the pH in the composter must be in the range of 4.5-6.5. This composter is designed to be able to carry out automatic mixing equipped with a temperature control system that serves to maintain temperature stability in the compost media according to the reference temperature. The composter design is equipped with a DHT 11 sensor as a temperature sensor, a pH sensor and the ESP 32 as the controller. Internet of Things (IoT) makes this system easy to control using android. Producing liquid organic fertilizer compered between the automatic and manual process. The results show that liquid organic fertilizer can be produced faster, has a better quantity and quality than the manual process.